ANALYSIS OF TOXIC LEADERSHIP AND ORGANIZATIONAL CYNICISM MEDIATED BY JOB BURNOUT ON TURNOVER INTENTION IN THE HYBRID WORK ERA - Herty Ramayanti Sinaga; Dhevi Dadi Kusumaningtyas; Alvi Noor Rahma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to clarify whether Job Burnout mediates the relationship between Toxic Leadership and Organizational Cynicism on Turnover Intention. The study deals with the study of Toxic Leadership and Organizational Cynicism in millennial generation employees. This research utilized quantitative methods by involving a sample of 100 millennial employees who work in the banking sector in Central Java Province taken with a purposive sampling technique and was assessed using a questionnaire instrument with a Likert scale of 1-5 points. Results indicated that toxic leadership has significant effects on job burnout and turnover intention. This means that toxic leadership is shown to predict job burnout which leads to turnover intention. Meanwhile, this study revealed that the burnout variable did not mediate the relationship between organizational cynicism and turnover intention. Further, organizational cynicism has no significant impact on the job burnout variable as per data retrieved from SEM. The paper is empirical and explain the psychological dynamics of millennial employees by giving more insights into it: so as to motivate the leadership style designs that control job burnout and turnover intentions.